Kajian Kelembagaan dalam Pengembangan Pariwisata Pantai yang Berkelanjutan - Kuhaja, Tendy (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2014)
Local Government Program in the development of tourism Wonokerto Beach is not maximized, but very crowded by tourists on Friday and Sunday. This raises the question of research on how to develop the existing institutional system of tourism component manager with the principles of sustainable institutions. This research uses the case study method. The analysis used is descriptive qualitative analysis. The results showed the identification of 15 stakeholders, management efforts have done, but still conducted themselves according to the level of interest and influence stakeholders. Based on the results of the study are also not found in the formal institutional Wonokerto coastal tourism development. So in order to be sustainable institutional development manager required coordination among stakeholders to achieve a common goal.